TRANSFORMATION OF THE LANGUAGE OF COMMUNICATION UNDER THE INFLUENCE OF SOCIETY’S INFORMATIZATION PROCESSES - Skyba, Ivan (Proceedings of the National Aviation University Series Philosophy Cultural, 2024)
Introduction. Modern society is experiencing significant changes due to the rapid advances in science and technology, as well as the integration of the latest information and communication technologies into various aspects of social practices. One of the most noticeable changes in contemporary society is the transformation of communication language, influenced by the processes of computerization and informatization. The aim and tasks. The article aims to identify how language transforms due to society’s informatization processes. Research methods. The theoretical and methodological basis of this research is general scientific and special methods and approaches, with the help of which the peculiarities of the transformation of the language of communication under the influence of the processes of informatization of society are investigated. Research results. The processes of informatization of society are accompanied by the development of the latest means of mass communication and the strengthening of their influence on several levels of the language system - lexical, grammatical, stylistic, etc. An important role in this process is played by the Internet, as today demonstrates a colossal difference in language facts found in two environments - virtual and real. That is, in the language used on the Internet and beyond. The forcing of communication processes leads to the simplification of language and speech in modern society. Discussion. The discussion analyzes the research of Roland Barthes. In his research, R. Barthes observed that there are connections between discursive systems that are established on power. He referred to a language system as a strong system that can operate in any circumstance and maintain its power, regardless of the actual number of native speakers. Conclusions. Solving the problem of improving speech culture lies primarily in education and requires a differentiated approach that considers modern societal trends.